The Arctic: Ecology and Hydrogen Electrical Power Engineering - R. N. Shulga; A. Y. Petrov; I. V. Putilova; Р. Н. Шульга; А. Ю. Петров; И. В. Путилова (Международный издательский дом научной периодики "Спейс, 2019)
The social and environmental aspects, climatic and glaciological features of the Arctic development in terms of energy supply are considered. The most expedient ways of complex development of the Arctic are shown. On the example of the large and unique stationary projects, paper marks some shortcomings: high cost, long-term construction, incomplete autonomy, insufficient solution of problems of ecology and waste processing. Incomplete autonomy is due to the need for transportation of materials, products, replacement crews and personnel, as well as insufficient logistics and transportation difficulties in summer on the mainland and in winter by sea. Problems of ecology and waste processing are associated with the use of traditional methods of burning solid and liquid fuels using coal or fuel oil polluting the environment. Switching to liquefied natural gas (LNG) for electric propulsion and power supply will significantly improve the environmental situation. The research performed on the mathematical model of the multifunctional energy complex of IEC shows the possibility of uninterrupted power supply of local load from both the centralized network, and from the diesel generator (DG) and the electric power storage; DG is used to save fuel as a backup source. The proposed technologies of power generation based on hydrogen or low-power nuclear power plants allow increasing the energy efficiency of the direct fuel conversion plant and provide integrated waste processing along with improving the environment. The small population of the Arctic, its mobility when using the rotational method requires the integrated development of mobile energy and life support systems of low power up to 30 MW using LNG or low-power nuclear power plants supplemented with RES. If the installation on hydrogen is both source and storage of electricity, the use of low-power nuclear power plants and especially RES require the use of energy storage devices. These hydrogen or electrochemical cycle storage devices are the most progressive in the ...